DEVELOPMENT OF WEB-BASED LEARNING PLANNING COURSE MEDIA FOR SUPPORT COLLEGE STUDENTS' LEARNING INDEPENDENCE - Hanifah, Nur Hidayah; Putri, Candra Avista (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
The lecture process in the university environment is inseparable from the use of technology. The purpose of this research is to develop web-based learning planning course media, to determine the feasibility of web-based learning media through validity tests and effectiveness tests. This type of research and development is research and development using the ADDIE model, namely Analyze to determine and analyze needs, Design select and design media, Develop carry out the development process and test validity, Implement apply to students, Evaluation of the overall process to improve the media to be better. This study produced learning planning course media for UIN Malang students who had gone through the validation test stages from design experts obtained 92%, material experts 88%, and learning experts by 96%. Meanwhile, the response from students to the media was 86% with a very practical category. Based on the test results that have been obtained, it can be concluded that website-based learning media can be declared valid and effective in the learning process in the classroom.